Lentil adaptation to drought stress: response, tolerance, and breeding approaches - Noor, Md. Mahmud Al; Tahjib-Ul-Arif, Md.; Alim, S. M. Abdul; Islam, Md. Mohimenul; Hasan, Md. Toufiq; Babar, Md. Ali; Hossain, Mohammad Anwar; Jewel, Zilhas Ahmed; Murata, Yoshiyuki; Mostofa, Mohammad Golam (Frontiers in Plant Science, 2024)
Lentil (Lens culinaris Medik.) is a cool season legume crop that plays vital roles in food and nutritional security, mostly in the least developed countries. Lentil is often cultivated in dry and semi-dry regions, where the primary abiotic factor is drought, which negatively impacts lentil growth and development, resulting in a reduction of yield. To withstand drought-induced multiple negative effects, lentil plants evolved a variety of adaptation strategies that can be classified within three broad categories of drought tolerance mechanisms (i.e., escape, avoidance, and tolerance). Lentil adapts to drought by the modulation of various traits in the root system, leaf architecture, canopy structure, branching, anatomical features, and flowering process. Furthermore, the activation of certain defensive biochemical pathways as well as the regulation of gene functions contributes to lentil drought tolerance. Plant breeders typically employ conventional and mutational breeding approaches to develop lentil varieties that can withstand drought effects; however, little progress has been made in developing drought-tolerant lentil varieties using genomics-assisted technologies. This review highlights the current understanding of morpho-physiological, biochemical, and molecular mechanisms of lentil adaptation to drought stress. We also discuss the potential application of omics-assisted breeding approaches to develop lentil varieties with superior drought tolerance traits.